Evaluation of an electrostatic precipitator in mitigating the transmission of airborne viruses in experimentally infected pigs - Lan Wang; José Morán; My Yang; Bernard A. Olson; Christopher J. Hogan; Montserrat Torremorell (Veterinary Research)
Abstract Airborne viruses spread rapidly in animal premises, which makes them difficult to contain. Electrostatic precipitators (ESP) are air cleaning devices that charge airborne particles and electrophoretically deposit them on collection surfaces, thereby removing them from an airstream. We evaluated the effect of a single-stage wire-plate ESP on mitigating airborne transmission of influenza A virus (IAV) and porcine reproductive and respiratory syndrome virus (PRRSV), using experimentally infected pigs. Inoculated pigs were placed in isolators upstream of the ESP, and sentinel pigs were placed downstream in an isolator. The airflow moved unidirectionally from inoculated pigs to sentinel pigs. Nasal swabs of pigs, air samples and surface wipes from all the isolators were collected daily and tested by RT-qPCR. Without the ESP powered, sentinel pigs tested positive within 1 day of exposure to IAV aerosols and 2 days to PRRSV aerosols. Airborne IAV RNA was detected upstream and downstream of the ESP in particles ranging from 0.22 μm to > 8 μm. In contrast, with the ESP powered, sentinel pigs tested positive after 5–6 days of exposure to IAV aerosols, and 7–8 days to PRRSV aerosols. Limited levels of IAV RNA were detected in air samples in the downstream isolator before sentinel pigs tested positive. The RNA-based virus removal efficiency of the ESP ranged from 96.91 to 99.97%, with higher removal observed in particles > 6.5 μm. Under the conditions of this study, the ESP efficiently removed IAV aerosol particles and delayed the onset of IAV and PRRSV infections in the sentinel pigs. Our study shows the potential of the ESPs to help prevent the spread of airborne viruses in agricultural animal farming facilities.